The Impact of Puppet Show Media on Grade 3 Students' Listening Skills at SDN 1 Syamtalira Bayu - Firdha Dwi Apriani; Maya Safitri; Jumat Barus (Genderang Asa: Journal of Primary Education, 2023)
The low creativity of teachers in determining learning media makes students experience difficulties in listening. One of the things that underlies the achievement of learning is the availability of media in the teaching and learning process. Therefore, the researcher formulated this study with the title "The Influence of Puppet Show Media on Students' Listening Skills in Theme 2 Class 3 SDN 1 Syamtalira Bayu". The purpose of this study was to determine whether or not there was an effect of the use of puppet show media on listening skills in grade III elementary school students. The method used is quantitative with a quasi-experimental approach. Sources of research data were all grade III of SDN 1 Syamtalira Bayu, totaling 21 students in the experimental class and 21 students in the control class. The data collection technique in this study was a test with the results of the research that there was an influence by using Puppet Show media on the listening ability of class III students. In testing the hypothesis, the price of tcount is 2,164 and ttable is 1,683 after testing at a significant level α = 0.05/2 and df = 40 based on the criteria for testing the hypothesis, then reject H0, because tcount > table, namely 2,164 > 1,683, then Ho is rejected, Ha is accepted, which means there is an influence in the use of puppet show media on students' listening skills on the theme of class 2 class III SDN 1 Syamtalira Bayu.